Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle - Anderson, William D., Jr.; Greene, Brian D.; Rocha, Luiz A. (Zootaxa, 2016)
In May 2014, a group of ichthyologists from the California Academy of Sciences and the Bishop Museum collecting fishes off the coast of Batangas, Luzon, Philippine Islands, obtained, in a depth of ca. 150 meters, four specimens of a species of Grammatonotus previously unknown to science. This new species, Grammatonotus brianne, is distinguishable from its described congeners by the following combination of characters: short anal-fin spines, rhomboid shaped caudal fin, lateral line usually disjunct, and live coloration. Herein we provide characters that distinguish callanthiids from other percoids and that distinguish Grammatonotus from Callanthias, the other genus in the family Callanthiidae, along with the description of the new species and short accounts of two other Grammatonotus, G. crosnieri and G. roseus, from the Coral Triangle.